An Immunological Stairway to Severe Tissue Complication Assembly in Bothrops atrox Snakebites - Ibiapina, Hiochelson Najibe Santos; Costa, Allyson Guimarães; Sachett, Jacqueline Almeida Gonçalves; Silva, Iran Mendonça; Tarragô, Andréa Monteiro; Neves, Juliana Costa Ferreira; Kerr, Marllon Wendell Athaydes; Santana, Monique Freire; Martins-Filho, Olindo Assis; Lacerda, Marcus Vinícius Guimarães; Ferreira, Luiz Carlos Lima; Malheiro, Adriana; et al. (Frontiers in Immunology, 2019)
Snakebites are a serious public health problem and, in the Amazon, the Bothrops atrox snake is the most frequent cause of envenomation. B. atrox venom (BaV) causes pathophysiological changes with intense, local inflammatory processes, such as severe tissue complication (STC). However, mechanisms associated with the inflammatory process in humans are still poorly understood. Thus, in this study, we sought to describe the profile of local and systemic immunological soluble molecules in Bothrops envenomation patients treated at a specialist tertiary healthcare unit in the Brazilian Amazon. An analytical and prospective study was performed with patients who had snakebites with different clinical outcomes (STC and Mild Tissue Complication - MTC) using venous blood and blister exudate in order to measure immunological soluble molecules present in the response process. Twenty STC patients and 20 MTC patients were eligible for the study. In addition, 20 healthy donors (HD) who had never been bitten by a snake were used as controls. The biomarkers CXCL-8, CCL-5, CXCL-9, CCL-2 and CXCL-10; C3a, C4a and C5a; IL-1, IL-2, IL-4, IL-5, IL-6, IL-10, TNF, IFN-γ and IL-17A were quantified using flow cytometry and ELISA. The circulating response profile differs between the studied groups, with MTC patients presenting a mixed profile and STC patients presenting a more polarized profile for Th1 response. In addition, individuals who develop STC have a more intense local immune response, because the tissue response differs from the circulating immunological soluble molecules and presents Th1/Th2/Th17 response polarization. Furthermore, these results suggest that CCL-2 and CXCL-10 are biomarkers for STC and the response profile they assume against Bothrops snakebite should reflect in the clinical practice for the patient.